Efficacy of Negative Pressure Wound Therapy on Thoracic Wounds After Esophagectomy (Medical Forum Monthly, 2022)
Objective: To evaluate the efficacy and effectiveness of NPWT in healing thoracic infections after esophagectomy in comparison with traditional open wound therapy.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Bakhtawar Amin Medical & Dental College & Hospital Multan from 10th July 2021 to Jan 10th 2022.Materials and Methods: A total of 100 patients with oesophagal cancer were included in the study who underwent esophagectomy. Only 30 patients were selected for final analysis, among which 20 patients were treated with NPWT and 10 patients were administered open wound therapy. The NPWT device was operated by inserting a drainage tube in the wound. None of the patients reported any complaints about the procedure. The remaining 10 patients were administered traditional wound dressing. After the growth of granulation tissue and the infection was minimized, patients were discharged. The dressing change was done in the outpatient department.Results: The rate of infection in our study was 30%. No patients showed any adverse reaction to the NPWT. All the patients treated with NPTW showed complete and successful wound healing. Patients experienced anastomotic leak and pneumonia as postoperative complications. The body temperature after the procedure and hospital stay did not differ significantly between both groups. However, the healing time of patients treated with NPTW was shorter I.e 12 days as compared to the other group i.e. 19 days.Conclusion: Facilitated NPTW is a safe, inexpensive and effective method for the treatment of thoracic wounds in comparison with open wound therapy.